GENE EXPRESSION AND mRNA SECONDARY STRUCTURES IN DIFFERENT Mycoplasma SPECIES - V. S. Sokolov; V. A. Likhoshvai; Yu. G. Matushkun (Вавиловский журнал генетики и селекции, 2015)
Evaluation of gene expression efficiency in different organisms is a vital task of modern biology. Microorganisms that feed on humans and pets are particularly interesting. In this work, bioinformatical analysis of 62 Mycoplasma strains is performed. It has been shown that translation efficiency in these organisms depends on the number of potential secondary structures in genes and does not depend on codon compositions. Several species with low concentrations of local inverted repeats in genes have been found. Phylogenetic analysis shows that this feature may be associated with their environment. High concentrations of local inverted repeats, not typical of other Mycoplasma species, have been found in the translation start regions of M. haemofelis genes.